Fetal hemoglobin levels are related to metabolic control in diabetic subjects - Pardini,V.C. (1999)
We have investigated the relationship between fetal hemoglobin (HbF) levels and metabolic control in subjects with insulin-dependent (N = 79) and non-insulin-dependent diabetes mellitus (N = 242). HbF and hemoglobin A1c (HbA1c) levels were increased in subjects with type 1 and type 2 diabetes as compared to levels in nondiabetic individuals (P<0.0001), and were significantly higher in type 1 than in type 2 diabetes subjects. Lower levels of HbA1c and HbF were observed in type 2 diabetes subjects treated by diet, intermediate levels in those treated with oral hypoglycemic agents, and higher levels in those treated with insulin. HbF and HbA1c levels were correlated in type 1 diabetes (R2 = 0.57, P<0.0001) and type 2 diabetes (R2 = 0.58, P<0.0001) subjects. Following intense treatment, twelve diabetic patients showed significant improvement both in HbA1c and HbF values. We conclude that increased HbF levels reflect poor metabolic control in subjects with diabetes mellitus.